PELATIHAN PEMBUATAN SOAL INTERAKTIF DENGAN PROGRAM WONDERSHARE QUIZ CREATOR BAGI GURU SEKOLAH DASAR DI KOTA MAGELANG - Purnanto, Arif Wiyat; Mahardika, Astuti (Universitas Muhammadiyah Surakarta, 2016)
This devotion was followed by the teachers of Kedungsari 1 and Kedungsari 5 in pupose of improving the understanding, skills, and innovation in formulating evaluation items using Wondershare Quiz Creator. It included training activities to create interactive questions with multiple choice items and fill in the blank. The results revealed that all participants were able to design interactive items in order to have varied and enjoyable evaluations. Besides, the teachers could design computer-based and paper-based items at the same time.Â